Academic writing for IT students - Artamonova, Lidiya V. (Издательство Томского государственного университета, 2023)
This textbook is intended for Master and PhD Information Technology students (B1-C1 level of English proficiency). The instructions of how to write a research paper in English and the relevant exercises are given. The peculiarities of each section of a paper are presented. The exercises are based on real science materials taken from peer-reviewed journals. The subject area covers a wide scope of different Information Technology domains.